(untitled) (Revista Contexto & Educação, 2023)
The formation of social, critical and autonomous conscience is one of the fundamental attributions of the University in its commitment to building a society founded on social justice and science. The present study aimed to identify the political conception of higher education students and relate it to their socioeconomic, cultural and academic characteristics, through a structured questionnaire. The study analyzed the responses of 290 students, most of them female, religious, former high school students, "non-quota", white, with little participation in political parties and the student movement. Overall, students demonstrated a progressive view, sensitive to issues of appreciation of the role of the state, justice and social equity. There are traces of intolerance and discrimination between religious and privatizing ideas and contrary to quotas between men, religious, non-quota students and students who attended high school in private schools. Despite the evidence from the study of university graduates with the prospect of positive changes in social relations, the current context experienced in the country, involved with the loss of rights and privatization of the state, should stimulate struggles in these groups for the maintenance of democracy and constitutional prerogatives.